Estimating Receiver Operative Characteristic Curves for Time-dependent Outcomes: The Stroccurve Package. (January 2017) - Cattaneo, Mattia; Malighetti, Paolo; Spinelli, Daniele
Receiver operating characteristic (ROC) curves are an established method for assessing the predictive capacity of a continuous biomarker for a binary outcome. However, in some cases, outcomes are time dependent. Although the literature has proposed packages for performing ROC analysis of time-independent outcomes, a package is not yet available for analyzing the predictive capacity of continuous biomarkers when the binary outcome is time dependent. In this article, we presentstroccurve, a new command for performing ROC analysis within a survival framework.